Topological Insulators. - Franz, Marcel; Molenkamp, Laurens; ScienceDirect eBooks (Burlington : Elsevier Science, 2013)
Topological Insulators, volume six in the Contemporary Concepts of Condensed Matter Series, describes the recent revolution in condensed matter physics that occurred in our understanding of crystalline solids. The book chronicles the work done worldwide that led to these discoveries and provides the reader with a comprehensive overview of the field. Starting in 2004, theorists began to explore the effect of topology on the physics of band insulators, a field previously considered well understood. However, the inclusion of topology brings key new elements into this old.
4.1 Defining the 3D Topological Insulator with Interactions4.2 Superconducting Proximity Effect; 4.3 Fractional Topological Insulators; 4.4 Related States in Three Dimensions; Acknowledgments; References; 3 Models and Materials for Topological Insulators; 1 Introduction; 2 HgTe Quantum Wells and the Bernevig-Hughes-Zhang Model; 3 Effective Model of the Three-Dimensional Topological Insulator; 4 Helical Edge/Surface State of 2D/3D Topological Insulators; 5 Physical Properties of Topological Edge/Surface States.
Print version record.
Elsevier
Keywords: Condensed matter; Topological dynamics; SCIENCE -- Energy; SCIENCE -- Mechanics -- General; SCIENCE -- Physics -- General; Condensed matter; Topological dynamics; Electronic books